Patient Perspective on Robotic-Assisted Total Joint Arthroplasty - Siddhartha Dandamudi, BBA; Kyleen Jan, MD; Madelyn Malvitz, BS; Anne DeBenedetti, MSc; Omar Behery, MD, MPH; Brett R. Levine, MD, MS (Arthroplasty Today)
Background: Robotic-assisted total joint arthroplasty (TJA) has gained popularity in recent years. Despite mixed patient and surgeon perceptions, conflicting evidence regarding efficacy and cost-effectiveness in comparison to manual TJA exists. Patients' beliefs surrounding robotic-assisted TJA remain unclear. This study aims to assess patients' expectations on robotic technology in TJA. Methods: A 9-question survey assessing patient understanding and expectations of the use of robotics in TJA was distributed to preoperative and postoperative hip and knee patients of five surgeons at a high-volume academic center. Responses were descriptively analyzed. Results: A total of 498 responses were collected. Of all respondents, 69.1% are aware of robotic usage in TJA, 68.5% are interested but unsure of the benefits, and only 19.5% feel it is superior to manual surgery. Most patients did not consider robotic TJA as minimally invasive surgery, with 61.7% stating they are not the same. In addition, 52.3% were not comfortable with extra or longer incisions for robotic procedures. Regarding surgeon choice, 94.9% did not consider if the surgeon is able to perform robotic TJA, 74.4% wanted their surgeon proficient in manual TJA, and 72.4% felt that surgeons who use robotic technology are not more capable than manual surgeons. Conclusions: Awareness and curiosity of robotic-assisted TJA exists; however, most patients did not appear to acknowledge superiority or benefits over manual surgery. Furthermore, patients appear to prefer surgeon proficiency in manual techniques, which may influence training programs in the future. Surgeons should weigh patient goals, expectations, outcomes, and costs when choosing to perform robotic TJA.